Preparation method of RuNi / MoS2 nanocatalyst for hydrogen production by hydrolysis of dimethylamine borane
By preparing RuNi/MoS2 nanocatalysts, the problem of low catalytic activity of existing catalysts is solved, and high efficiency catalytic hydrolysis of dimethylaminoborane is achieved to produce hydrogen, with good stability and high TOF value.
Patent Information
- Application Number
- CN202310043946.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-01-29
AI Technical Summary
The existing dimethylaminoborane hydrolysis catalysts have low catalytic activity, and their catalytic performance and stability are not sufficient to meet the needs of large-scale applications.
RuNi/MoS2 nanocatalysts were prepared by simple chemical reduction method by commercially used MoS2, sodium borohydride, ruthenium trichloride and nickel hexahydrate as raw materials. The method includes dissolving MoS2 in ionic water, adding ruthenium salt and nickel salt, sonication treatment, adding sodium borohydride solution, stirring the reaction, and then centrifuging and washing to obtain RuNi/MoS2 nanocatalyst.
The prepared RuNi/MoS2 nanocatalyst has high hydrolysis activity and good stability, and can effectively catalyze the hydrolysis of dimethylaminoborane to produce hydrogen. The TOF value reaches 7199mol(H2)·molcat-1·h-1, which is much higher than the TOF value of Ru/MoS2 and Ni/MoS2 catalysts alone.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a RuNi / MoS for producing hydrogen by hydrolysis of dimethylamine borane. 2 The invention discloses a method for preparing a nano catalyst, belonging to the technical field of nano catalyst. Background Art
[0002] In recent years, due to the damage of fossil fuels to the environment, the sustainability of energy systems and policies has received increasing attention. In this context, hydrogen (H 2 ) is considered to be a clean, safe and environmentally friendly energy carrier that can be stored in a solid form in borane adducts. Ammonia borane, sodium borohydride, hydrazine borane and dimethylamine borane are boron-based compounds that are considered to be solid hydrogen storage materials. Among them, dimethylamine borane is a very promising candidate material due to its stability and low regeneration cost. However, the catalytic activity of most DMAB hydrolysis catalysts is still low, and the catalytic performance and stability are far from meeting the needs of large-scale applications. Therefore, the rational design and construction of catalysts is still one of the most challenging issues in promoting DMAB hydrolysis to produce hydrogen. Here, the present invention uses a simple chemical reduction method to prepare a solid hydrogen storage material using commercial MoS 2 The alloy nanocatalyst RuNi / MoS was prepared by using sodium borohydride, ruthenium trichloride and nickel nitrate hexahydrate as raw materials. 2 Used for the hydrolysis and dehydrogenation of dimethylamine borane. Summary of the invention
[0003] In view of the above technical problems, the present invention provides a RuNi / MoS for hydrogen production by hydrolysis of dimethylamine borane. 2 The method for preparing a nanocatalyst comprises the following steps:
[0004] Step 1: MoS 2 Add deionized water to dissolve, then add ruthenium salt and nickel salt, and treat with ultrasound for 5-10 minutes to make them disperse evenly.
[0005] Step 2: Dissolve sodium borohydride in deionized water, add the solution dropwise into the above step (1), and stir to react for 5-10 minutes.
[0006] Step 3: After the reaction is completed, centrifuge and wash to obtain ruthenium nickel alloy nanocatalyst RuNi / MoS 2 .
[0007] The MoS 2 The molar ratio of ruthenium in the ruthenium salt to nickel in the nickel salt is: 0.2-0.3:3-5:1-3.
[0008] The ruthenium in the ruthenium salt is ruthenium trichloride, and the nickel in the nickel salt is nickel nitrate hexahydrate.
[0009] The MoS 2 Can be replaced by Co 3 O 4 、CeO 2 、ZrO 2 , Fe 3 O 4 , or ZnO.
[0010] The molar ratio of the reducing agent sodium borohydride to the metal ions in the metal salt is 10-15:1.
[0011] The present invention also relates to the application of the RuNi / MoS2 alloy nanocatalyst as a hydrogen production process for hydrolyzing dimethylamine borane. The catalyst has the advantages of high hydrolysis activity, good stability, and being easy to obtain.
[0012] The complete hydrolysis equation of dimethylamine borane is:
[0013] Me 2 NHB 3 +2H 2 O→Me 2 NH 2 BO 3 +3H 2 ↑
[0014] In the application of catalytic hydrolysis of dimethylamine borane to produce hydrogen, it has a high catalytic selectivity, and its activation energy value is 48.4KJ / mol. The TOF of the first 2 minutes of the reaction can be calculated
[0015]
[0016] Where t = 2min, mL H2 is the volume of hydrogen produced in 2 minutes of reaction, and TOF = 7199 mol (H 2 )·mol cat -1 ·h -1 .
[0017] The present invention also has the following beneficial effects: for catalyzing the hydrolysis of dimethylamine borane to produce hydrogen, currently most of the catalysts are synthesized by using dual precious metals, so the RuNi / MoS2 alloy nanocatalyst is relatively inexpensive, and the synthesized alloy nanoparticles are evenly distributed, have a fast catalytic reaction speed, and have the advantages of high stability. It can catalyze the hydrolysis of dimethylamine borane to produce hydrogen, showing a good development trend and broad application prospects.
[0018] In order to further highlight the advantages of the prepared catalyst, Ru / MoS 2 、Ni / MoS 2 The results showed that the use of Ru / MoS2 、Ni / MoS 2 As catalyst, dimethylamine borane was hydrolyzed to produce hydrogen, and the TOF values were 6429 mol (H 2 )·mol cat -1 ·h -1 and 201mol(H 2 )·mol cat -1 ·h -1 , while RuNi / MoS 2 Catalyzes dimethylamine borane to produce hydrogen, with a TOF value of 7199 mol (H 2 )·mol cat -1 ·h -1 , much higher than Ru / MoS 2 and Ni / MoS 2 This also shows that the catalyst of the present invention has such a good effect because there is electron transfer between the two metals in the catalyst, resulting in a synergistic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Ru / MoS 2 、RuNi / MoS 2 XRD pattern of .
[0020] Figure 2 RuNi / MoS 2 Lattice spacing diagram of the nanocatalyst.
[0021] Figure 3 RuNi / MoS 2 TEM image of the nanocatalyst after 5 cycles.
[0022] Figure 4 RuNi / MoS 2 Particle size distribution of nanocatalyst before and after recycling.
[0023] Figure 5 RuNi / MoS 2 XPS pattern of ruthenium in nanocatalyst.
[0024] Figure 6 RuNi / MoS 2 XPS pattern of nickel in nanocatalyst.
[0025] Figure 7 The effect of substrate concentration on hydrolysis kinetics.
[0026] Figure 8 The effect of catalyst concentration on hydrolysis kinetics.
[0027] Fig. 9 The effect of temperature on hydrolysis kinetics.
[0028] Fig.10 RuNi / MoS 2 Nanocatalyst cyclic performance test.
[0029] Fig.11 The effect of RuNi nanoparticles loaded on different carriers on the catalytic performance.
[0030] Fig.12 Zn 2+ / EDTA-2Na as RuNi / MoS 2 The influence of nanocatalyst on the "on-off" of hydrogen production from dimethylamine borane. DETAILED DESCRIPTION
[0031] In order to better explain the present invention, the following is a RuNi / MoS 2 The preparation of nanocatalysts and their applications are further explained.
[0032] Example 1
[0033] Step 1: Ruthenium trichloride (RuCl 3 ) was dissolved in deionized water and stirred to dissolve to obtain Ru 3+ Aqueous solution 0.04mmol / L;
[0034] Step 2: Nickel chloride hexahydrate (NiCl 2 6H 2 O) was dissolved in deionized water and stirred to dissolve to obtain Ni-containing 2+ Aqueous solution 0.04mmol / L;
[0035] Step 3: 40 mg of MoS 2 Add 8.5 mL of deionized water and stir thoroughly;
[0036] Step 4: Take the Ru from step 1 and step 2 3+ Aqueous solution (0.4 mL) and Ni 2+ The aqueous solution (0.2 mL) was added to the MoS 2 Dispersion, ultrasonic stirring for 10-15min;
[0037] Step 5: Rapidly add 1 mL of 0.3 mmol / mL sodium borohydride solution to the solution obtained in step 4, and stir the reaction for 10-15 minutes until the reaction is complete;
[0038] Step 6: Wash and centrifuge the precipitate obtained in step 5 to prepare RuNi / MoS 2Alloy nanocatalysts.
[0039] Step 7: The same method was used to prepare RuNi nanoparticles supported on different carriers (RuNi / MoS 2 、RuNi / Co 3 O 4 、RuNi / CeO 2 、RuNi / ZrO 2 、RuNi 0.2 / Fe 3 O 4 , RuNi / ZnO).
[0040] Figure 1 The XRD pattern of the ruthenium nickel nanocatalyst prepared in Example 1 of the present invention shows that RuNi / MoS 2 , characteristic diffraction peaks and MoS 2 There is no visible peak of RuNi surface, mainly because its alloy nanoparticles are small and have not formed a good shape, thus there is no characteristic peak.
[0041] Figure 2 RuNi / MoS prepared in Example 1 2 The lattice spacing diagram of the nanocatalyst shows that the catalyst contains RuNi(101) alloy with a lattice spacing of 0.199 nm. 2 The interplanar spacing of the (105) crystal plane is 0.18 nm.
[0042] Figure 3 RuNi / MoS prepared in Example 1 2 TEM image of the nanocatalyst after five cycles shows that the dispersed morphology of the nanoparticles after the cycle is located in the MoS 2 Edge position.
[0043] Figure 4 The RuNi / MoS prepared in Example 1 of the present invention 2 The particle size distribution of the nanocatalyst before and after the cycle. It can be seen from the figure that the nanoparticle size does not change much before and after the cycle, indicating that the prepared RuNi / MoS 2 Nanocatalyst is a good heterogeneous catalyst.
[0044] Figure 5 The RuNi / MoS prepared in Example 1 of the present invention 2 The XPS graph of ruthenium in the nanocatalyst proves that the catalyst contains the Ru element, and Ru exists in the catalyst in a zero-valent state. The binding energy of zero-valent ruthenium is located at 463.7 eV and 486.2 eV.
[0045] Figure 6 The RuNi / MoS prepared in Example 1 of the present invention 2 XPS graph of nickel in nanocatalyst. The graph shows that the catalyst contains nickel. Since the nickel surface is easily oxidized, nickel exists in the catalyst in divalent and zero-valent states. The binding energy of divalent nickel is located at 858.46eV and 876.12eV, and the binding energy of zero-valent nickel is located at 856.38eV and 873.76eV.
[0046] Example 2
[0047] RuNi / MoS 2 The dependence of the hydrogen production kinetics of nanocatalysts on dimethylamine borane on the substrate concentration. The steps are as follows:
[0048] Step 1: Take the RuNi / MoS prepared in Example 1 2 The nanocatalyst was placed in the reactor, and then 4 mL of sodium hydroxide aqueous solution (2 M) was added, and a magnetic bar was added. The reactor was sealed and placed in a heat-collecting constant temperature heating magnetic stirrer (30° C.), and stirred for 10 min;
[0049] Step 2: Dissolve dimethylamine borane in deionized water to prepare solutions of different concentrations: 0.75 mmol / mL, 1.00 mmol / mL, 1.25 mmol / mL, and 2 mmol / mL.
[0050] Step 3: Use a syringe to draw 1 mL of the dimethylamine borane solution of different concentrations prepared in step 2, and quickly inject it into the reactor in step 1. Start timing at the same time, and record the hydrogen volume at the corresponding time every 30 seconds. Figure 7 As shown, the TOF values of 0.75mmol / mL, 1.00mmol / mL, 1.25mmol / mL and 2mmol / mL dimethylamine borane at 2min were 4803mol(H 2 )·mol cat -1 ·h -1 , 6155mol(H 2 )·mol cat -1 ·h -1 , 7199mol(H 2 )·mol cat -1 ·h -1 , 8182mol(H 2 )·mol cat -1 ·h -1, and its fitting slope is close to 0, indicating that the relationship between its hydrolysis reaction and its substrate concentration is a zero-order reaction, and it has little dependence on the concentration of the substrate.
[0051] Example 3
[0052] RuNi / MoS 2 Nanocatalysts were used to study the dependence of hydrogen production kinetics of dimethylamine borane on catalyst concentration. The steps are as follows:
[0053] Step 1: Prepare RuNi / MoS with different metal contents 2 Nanocatalyst: 0.5%, 1%, 1.5%, 2%.
[0054] Step 2: Prepare the RuNi / MoS with different metal contents in step 1 2 The nanocatalyst was placed in a reactor, and then 4 mL of sodium hydroxide aqueous solution (2 M) was added, and a magnetic bar was added. The reactor was sealed and placed in a heat-collecting constant temperature heating magnetic stirrer (30° C.), and stirred for 10 min;
[0055] Step 3: Use a syringe to draw 1 mL of dimethylamine borane solution (1 mmol / mL) and quickly inject it into the reactor. Start timing at the same time and record the hydrogen volume at the corresponding time every 30 seconds. Figure 8 As shown, 0.5%, 1%, 1.5%, and 2% RuNi / MoS 2 The TOF values of the alloy nanocatalysts at 2 min were 6363 mol(H 2 )·mol cat -1 ·h -1 , 7199mol(H 2 )·mol cat -1 ·h -1 , 6065mol(H 2 )·mol cat -1 ·h -1 , 447 mol(H 2 )·mol cat -1 ·h -1 The hydrolysis of dimethylaminoborane is fitted into a first order curve, indicating that the relationship between its hydrolysis reaction and its catalyst concentration is a first order reaction. The higher the catalyst concentration, the faster the reaction rate.
[0056] Example 4
[0057] RuNi / MoS 2 The temperature dependence of the hydrogen production kinetics of alloy nanocatalysts applied to dimethylamine borane. The steps are as follows:
[0058] Step 1: Put the RuNi / MoS2 nanocatalyst prepared in Example 1 into a reactor, add 4 mL of sodium hydroxide aqueous solution (2 M), add a magnet, seal the reactor and place it in a heat-collecting constant temperature heating magnetic stirrer, set different reaction temperatures: 25°C, 30°C, 35°C, 40°C, and stir for 10 min;
[0059] Step 2: Use a syringe to draw 1 mL of dimethylamine borane solution (1 mmol / mL) and quickly inject it into the reactor. Start timing at the same time and record the hydrogen volume at the corresponding time every 30 seconds. Fig. 9 As shown in the figure, the TOF values at 25℃, 30℃, 35℃, and 40℃ at 2 min were 3884 mol(H 2 )·mol cat -1 ·h -1 , 7199mol(H 2 )·mol cat -1 ·h -1 , 8705mol(H 2 )·mol cat -1 ·h -1 , 8873mol(H 2 )·mol cat -1 ·h -1 The hydrolysis of dimethylaminoborane is fitted into a first order curve, indicating that the relationship between the hydrolysis reaction and the temperature is a first order reaction. The higher the temperature, the faster the reaction rate.
[0060] Example 5
[0061] RuNi / MoS 2 Alloy nanocatalysts were used to test the kinetics of hydrogen production from dimethylamine borane and the cycle performance. The steps are as follows:
[0062] Step 1: Take the RuNi / MoS prepared in Example 1 2 The nanocatalyst was placed in the reactor, and then 4 mL of sodium hydroxide aqueous solution (2 M) was added, and a magnetic bar was added. The reactor was sealed and placed in a heat-collecting constant temperature heating magnetic stirrer (30° C.), and stirred for 10 min;
[0063] Step 2: Use a syringe to draw 0.5 mL of dimethylamine borane solution (2 mmol / mL) and quickly inject it into the reactor. Start timing at the same time and record the hydrogen volume at the corresponding time every 30 seconds.
[0064] Step 3: After the above reaction is complete, inject 0.5 mL of dimethylamine borane (2 mmol / mL) into the reactor again and record the volume of hydrogen again. Repeat this step for 5 times. As shown in Figure 10, the TOF value of the first reaction at 2 min was 6899 (H 2 )·mol cat -1 ·h -1 , and the TOF value can still reach 6290 (H 2 )·mol cat -1 ·h -1 As the number of catalytic times increases, the hydrogen production rate slows down slightly, but still has high catalytic activity. 2 The cycling performance of the nanocatalyst is good.
[0065] Example 6
[0066] RuNi / MoS 2 The effect of different carriers on the hydrogen production kinetics of nanocatalysts applied to dimethylamine borane. The steps are as follows:
[0067] Step 1: Place the catalyst prepared in Example 1 in a reactor, add 4 mL of sodium hydroxide aqueous solution (2 M), add a magnetic bar, seal the reactor and place it in a heat-collecting constant temperature heating magnetic stirrer (30° C.), and stir for 10 min;
[0068] Step 2: Use a syringe to draw 1 mL of dimethylamine borane solution (1 mmol / mL) and quickly inject it into the reactor. Start timing at the same time and record the hydrogen volume at the corresponding time every 30 seconds. Fig.11 As shown in the figure, the carrier is of great significance to RuNi alloy nanoparticles. The TOF values of different carriers at 2 min can be seen as RuNi / MoS 2 (7199h -1 )>RuNi / Co 3 O 4 (7089h -1 )>RuNi / CeO 2 (6027h -1 )>RuNi / ZrO 2 (5290h -1 )>RuNi / Fe 3 O 4 (1814h -1 )>RuNi / ZnO(301h -1 ), which indicates that MoS 2 It plays an important role in the hydrolysis of dimethylamine borane.
[0069] Example 7
[0070] Zn 2+ / EDTA-2Na as RuNi / MoS 2 The effect of nanocatalyst on the hydrogen production switch of dimethylamine borane. The steps are as follows:
[0071] Step 1: Place the catalyst prepared in Example 1 in a reactor, add 4 mL of sodium hydroxide aqueous solution (2 M), add a magnetic bar, seal the reactor and place it in a heat-collecting constant temperature heating magnetic stirrer (30° C.), and stir for 10 min;
[0072] Step 2: Use a syringe to draw 1 mL of dimethylamine borane solution (1 mmol / mL), and quickly inject it into the reactor of step 1. Start timing at the same time, record the hydrogen volume at the corresponding time every 15 seconds, and react for 1 minute.
[0073] Step 3: Add 0.1 mL of an aqueous solution of zinc nitrate (0.3 M) to step 2 to shut down the hydrolysis and hydrogen production reaction of dimethylamine borane for 2 minutes.
[0074] Step 4: Add 0.2 mL of EDTA-2Na (0.15 M) aqueous solution to step 3 to start the hydrolysis and hydrogen production reaction of dimethylamine borane. Fig.12 The Zn-EDTA-2Na has a significant "on-off" effect on the hydrogen production from the hydrolysis of dimethylamine borane, and has no effect on the catalytic activity of the catalyst. However, when only a single metal transition metal is loaded, there is basically no response in the on-off effect. If the method of Example 1 is used without adding an aqueous solution of ruthenium trichloride, the product obtained is Ni / MoS 2 Nanocatalyst. For example, if the method of Example 1 is used without adding an aqueous solution of ruthenium trichloride, and nickel chloride hexahydrate is replaced with CoCl2·6H2O, the obtained product is Co / MoS 2 Nanocatalyst. The obtained Ni / MoS 2 Nanocatalyst, Co / MoS 2 Nanocatalysts are unable to achieve the above switching effects.
Claims
1. Application of RuNi / MoS2 nanocatalyst in the hydrolysis of dimethylamine borane to produce hydrogen, characterized in that: The loading amount of metal RuNi in RuNi / MoS2 nanocatalyst was 0.5%, 1%, or 1.5%; The preparation method of RuNi / MoS2 nanocatalyst for producing hydrogen by hydrolysis of dimethylamine borane comprises the following steps: (1) Dissolve MoS2 in deionized water, then add ruthenium salt and nickel salt, and disperse them evenly by ultrasonication; (2) dissolving sodium borohydride in deionized water, adding the solution dropwise to the above step (1), and stirring to react; (3) After the reaction is completed, centrifugation and washing are performed to obtain ruthenium nickel alloy nanocatalyst RuNi / MoS2.
2. The use according to claim 1, characterized in that: The molar concentration of MoS2 described in step (1) is 0.2-0.3 mmol / ml.
3. The use according to claim 1, characterized in that: The molar ratio of ruthenium in the ruthenium salt to nickel in the nickel salt in step (1) is 3-5:1-3.
4. The use according to claim 1, characterized in that: The ruthenium salt in step (1) is ruthenium trichloride, and the nickel salt is nickel nitrate hexahydrate.
5. The use according to claim 1, characterized in that: The MoS2 described in step (1) is replaced by any one of Co3O4, CeO2, and ZrO2.
6. The use according to claim 1, characterized in that: The molar ratio of the reducing agent sodium borohydride to the metal ion in the metal salt in step (2) is 10-15:
1.
7. The use according to claim 1, characterized in that: The RuNi / MoS2 nanocatalyst is effective in achieving Zn 2+ / EDTA-2Na has an on-off effect on the hydrolysis of dimethylamine borane to produce hydrogen.
Citation Information
Patent Citations
Preparation method and application of titanium dioxide nano tube loaded dual-metal ruthenium and nickel nano catalyst
CN106378149A
Preparation method and application of MoS2 loaded Co nanoparticles
CN113000048A